(untitled) (Journal of Medical Device Technology, 2024)
There are lots of cases of injury or trauma that can cause broken or cracked bones. Long treatment can be more dangerous when combined with some of the diseases they have. Despite this, there is still not much research on the mechanical properties of bone, especially in the elderly. To develop bone tissue engineering and the design of bionic bones, it is essential to understand the mechanical properties and microscopic failure mechanisms of bones. Proper bone function also depends on the mechanical properties of the bone. The purpose of this study is to develop the three-dimensional bone model for finite element analysis simulation and examine the mechanical behavior of two different types of bone (normal and non-displaced transverse fracture bone) through ANSYS Workbench. The 3D bone model design of normal and cracked bone was imported, analyzed, and simulated in ANSYS with varying loads applied. To get the parameter of mechanical characteristics of bones to result. Application of finite element method using ANSYS Software as a computational technique that uses continuum mechanics theories to solve biomedical engineering problems may require the accurate analysis of the mechanistic properties of human bone. There was no significant difference in elastic modulus between normal and fractured bone. The maximum Young’s modulus was found at 8.225×10-7 with a minimum of 4.095×10-5. Despite this, the shear strain and stress hold a huge gap in the maximal and minimum position of both types of bone. Certainly, transverse fracture bone got the highest number of total deformations. The normal bone got 0.00023607 m for total deformation, alternatively, 0.00031965 m occurs in transverse fracture when the greatest load is performed. This clearly states, that cracked bone has a greater risk of failure and stiffness especially in elderly people. These mechanical properties findings of fractured bone are considered suitable for further development, especially in the prevention and treatment to decrease the revision of critical surgery in the future.